The Role of Generic Language in the Early Development of Social Categorization. Issue 1 (27th January 2017) - Rhodes, Marjorie; Leslie, Sarah‐Jane; Bianchi, Lydia; Chalik, Lisa
Abstract : Classifying people into categories not only helps humans simplify a complex social world but also contributes to stereotyping and discrimination. This research examines how social categorization develops by testing how language imbues with meaning otherwise arbitrary differences between people. Experimental studies ( N  = 129) with 2‐year‐olds showed that generic language—language that refers to abstract kinds—guides the development of social categorization. Toddlers learned a new category after hearing generic language about individuals who shared an arbitrary perceptual feature but not after hearing matched specific language, simple labels, or plural (but nongeneric) language about the same set of individuals. These findings show how subtle linguistic cues shape the development of social categorization.